What determines local governments' technical efficiency? The case of road maintenance - Alexander Kalb (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
In this paper we investigate the determinants of local governments' technical efficiency in road maintenance for a panel of German counties using a broad variety of estimation approaches. More specifically, we calculate efficiency indices using non-parametric (DEA) and parametric (stochastic frontier analysis) reference technologies, and examine how these efficiency indices can be explained by estimating and comparing four different regression models. The results of our analysis show that (controlling for numerous characteristics of the counties) the disposable income of the counties' citizens, intergovernmental grants (for county roads), and the payments to the counties influence efficiency negatively. Concerning political variables we find weak evidence that efficiency decreases with an increasing share of seats of left-wing parties in the county council; the hypothesis that efficiency decreases with the degree of political concentration in the county council could not be confirmed.
Keywords: H11; R30; R51; 330; Technical efficiency; road maintenance; stochastic frontier analysis; data envelopment analysis; German counties; Straßenbau; Kommunale Infrastruktur; Technische Effizienz; Kommunalverwaltung; Public Choice; Deutschland